Riscos ergonômicos e adoecimento no trabalho de enfermagem em foco: Hospital de Clínicas/UFU-MG - Soares, Patrícia de Cássia Araújo (2017)
The activity of the nursing team in the hospital environment is developed in the 24 hours without interruption and because it is always present and available in the workplace, the nursing professional has greater physical and / or psychic overload. This situation, in a continuous and prolonged way, contributes to the development of illnesses, illnesses and withdrawals that invariably impact the work and quality of life of this worker. Thus, it is necessary to reflect on their health, seeking to understand the relationship between work in the health area and the impacts on the quality of life of the nursing staff worker. The interest in the subject was manifested by the question about the reasons for the removals of the workers of the nursing team of the Medical Clinic of HC / UFU and if the ergonomic risks present in their work environment collaborate for these absenteeisms. The objective of this study was to identify, analyze, evaluate the perception and knowledge of the nursing team about the ergonomic risks and to evaluate the causes of illness and remoteness in the hospitalization unit of HC / UFU Clinic and the methodology used was the quali / quantitative . The results obtained did not fully confirm the initial hypothesis, but the high number of illnesses and departures due to musculoskeletal and psychic / emotional problems proved to be the correct methodological path. The knowledge of ergonomics and ergonomic risks by the ergonomic analysis of the work can contribute in the reduction and minimization of the nursing staff 's illnesses together with prevention, health promotion and improvements in working conditions.